Pengaruh Cangkang Pomacea canaliculata L Terhadap Sifat Fisika dan Kimia Air Sungai Cisadane - Maftukhah, Siti; Agustine, Dine; Amyranti, Mutia; Sukma, Andhika Cahaya Titisan (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
The Cisadane River is a very important ecosystem for the people of the city of Tangerang. Its utilization has the potential to produce waste that can damage aquatic life so that it becomes one of the sources of the problem of decreasing water quality both physically and chemically. One of the efforts made to overcome the problem of Cisadane river water is to use water purifiers derived from natural materials so that they do not endanger health and can bind heavy metals. The purpose of this study was to determine the effect of adding snail shells to the water quality of the Cisadane river in industrial areas, urban areas and slums in terms pH value, TDS value and Pb heavy metal. The experimental procedures in this study were snail shell preparation, Cisadane river water sampling, sample analysis before application, snail shell powder application, and sample analysis after application. The results of analys show that the clarity level of Cisadane river water ranges from 19 NTU to 59 NTU, the pH value ranges from 7.2 to 7.9, the TDS value ranges from 60 mg/l to 170 mg/l and the heavy metal content is 0.0047 mg /l. The conclusion of this research is that there is an increase in the level of clarity with the addition of snail shells by 45%, there is not visible effect of the snail shells addition’s on the pH value and content of Pb heavy metal. And there is an increase in the TDS value after adding snail shells.